THE ROLE OF PERCIVED FLOW AS A MEDIATION IN THE RELATIONSHIP BETWEEN WEBSITE QUALITY AND ONLINE BUYING INTEREST IN TRAVEL TRANSPORTATION SERVICES IN MALANG CITY - Stella Alvianna; Hidayatullah, Syarif (Ride: Journal of Cultural Tourism and Religious Studies, 2025)
Malang City, as one of the major cities in East Java, has high market potential for the use of online transportation services (online travel). The development of digital technology has driven the increase in the use of online travel booking platforms, where website quality is an important factor in shaping user perceptions and purchasing intentions. Previous research has shown that website quality has a significant effect on perceived flow and user purchasing intentions. Based on these findings, this study aims to analyze the influence of website quality dimensions—including usability, functionality, and security and privacy—on perceived flow and online purchasing intentions among users of travel transportation services in Malang City, and to examine the mediating role of perceived flow in this relationship. This study used a quantitative approach with a cross-sectional method. A total of 33 respondents who used online travel transportation services in Malang City were sampled. Data were collected through a Likert scale questionnaire (1–5) to measure website quality, perceived flow, and online purchasing intentions. Analysis was conducted using SPSS, including validity and reliability tests, descriptive analysis, correlation, multiple linear regression, and mediation tests using the Baron & Kenny and Sobel tests. The results showed that website functionality was the most dominant factor that significantly influenced perceived flow and online purchasing intentions. Conversely, website usability, security, and privacy had positive but insignificant effects. Furthermore, perceived flow did not act as a significant mediator. Overall, improving website functionality is a top priority in strengthening the digitalization strategy for online travel services in Malang City